Psycholinguistic Studies: Language Acquisition and Learning in 2-5 Year Old Children - Safi'i, Muhammad; Harahap, Rosmawaty (PT. Riset Press International, 2024)
The main focus of this research is to find out how language learning and language acquisition of children aged 2 to 5 years using a psycholinguistic study approach. The purpose of this study can be seen from the analysis documentation, interviews, and observations conducted by researchers in Sidomukti village, West Kisaran sub-district, Asahan Regency, North Sumatra Province. This study found that children acquire language in four phases. First, they have a babbling level (0.0-1.0). Second, they experience the holophrase period (1.0-2.0). Third, they enter the sensorimotor stage (from birth to 2-3 years old) and fourth, they enter the preoperative stage (from 3-5 years old). The data source is 15 children in Sidomukti village, West Kisaran sub-district, Asahan Regency, North Sumatra Province, aged 0 to 5 years old. The data found in this study includes children's language acquisition and language learning. Data collection methods included observation, interviews and recordings. The results showed that psycholinguistics correlates with children's language acquisition and learning.